Challenges and realities of early childhood development centers in Malawi: A critical examination - Lazarus Obed Livingstone Banda; Chigonjetso Victoria Banda; Jane Thokozani Banda (PLoS ONE, 2025)
The study on Early Childhood Development (ECD) practices in T/A Zilakoma, Nkhata Bay South Constituency, Malawi, employs the Ecological Systems Theory to explore recruitment, role definitions, and support systems. This theoretical construct enables an intricate examination of interactions within various environmental systems, emphasizing micro, meso, exo, macro, and chrono systems. Specifically, it illuminates the dynamics within immediate settings, interconnections among diverse systems, broader indirect influences, cultural ideologies, societal values, and temporal dimensions, offering a comprehensive lens for understanding educational contexts. The descriptive qualitative research was conducted within a case study framework to explore the practical experiences of stakeholders within ECD using semi-structured interview guides. Ethical standards were upheld, ensuring voluntary participation and confidentiality. Purposive sampling was used to collect data from diverse and knowledgeable participants involved in ECD domains, providing comprehensive insights aligned with the study’s objectives. Thematic analysis and sentiment mining were performed using Atlas 23 software. The results revealed themes such as recruitment practices relying on community-driven approaches, role ambiguity due to undefined responsibilities, informal evaluation processes, inconsistent training opportunities, and a dependency on community and volunteerism. These themes highlight the absence of formal structures and standardized processes in various aspects of ECD programs. Additionally, sentiment analysis illustrated diverse perspectives among stakeholders, reflecting their distinct experiences and challenges within the ECD landscape. The study concludes with policy recommendations aimed at addressing these systemic challenges.